(untitled) (Physical Education, Health and Social Sciences, 2024)
Agriculture is a vital sector of Pakistan’s economy and livestock is the subsector of agriculture. The country’s economy suffers as a result of the tick-parasitic disease, which also has an impact on the livelihood of the nation’s impoverished farmers and the dairy sector. This study was conducted to observe the prevalence of TBPDs in domestic ruminants in District Narowal, Pakistan. 1482 blood samples were collected by using sterilized disposable syringes in EDTA test tubes. Field staining was performed to observe blood under the microscope. The prevalence of TBPDs in domestic ruminants in District Narowal was 48.04%. The overall prevalence of Babesiosis, Theileriosis, and Anaplasmosis was 20.38%, 14.03%, and 13.63%, respectively. Location, gender, and age-wise comparison were observed. The percentage of Babesiosis was higher in ram (36%). The percentage of Theileriosis was higher in buffalo heifers i.e., 2-4years old (18.91%). The percentage of Anaplasmosis was higher in adult female buffaloes i.e., 14.77%. Babesiosis was higher in May i.e., 35.06%. Theileriosis (54.54%) and Anaplasmosis (23.95%) were higher in July and June, respectively. In the Narowal district, eight collecting sites from three tehsils were included: Narowal, Badomali, Domala, Shakargarh, Noorkot, Plot, Dhamthal, and Darman. Babesiosis is most prevalent in Plot (23.12%), whereas theileriosis and anaplasmosis are most prevalent in Dhamthal (19.69% and 15.69%, respectively) and Shakargarh (15.69%), respectively. To better detect these tick-borne parasites and allow for accurate diagnosis and treatment of ruminants, new techniques like PCR are advised to be applied.